Estimation of the familial relative risk of cancer by site from a French population based family study on colorectal cancer (CCREF study). Issue 9 (11th August 2004) - Andrieu, N; Launoy, G; Guillois, R; Ory-Paoletti, C; Gignoux, M
Abstract : Background: Colorectal cancer (CRC) is the second most common cause of death from cancer in France. A family history of CRC increases an individual's risk of developing CRC. Family history has been suggested to have a greater impact on proximal than distal tumours. Aim: We estimated the familial risk of CRC and other cancers, and examined how risk varies according to localisation of the tumour in the colorectal tract. Subjects: We recorded all cases of CRC diagnosed between 1993 and 1998 in the region served by the Calvados Cancer Registry. A trained interviewer asked all participants about their family history of cancer. Statistical methods: Familial risk was estimated from a cohort analysis of the relatives of the CRC cases. The expected numbers of cancers were calculated from Calvados incidence rates. Familial relative risks were calculated using standardised incidence ratios. Results: Our findings showed that colon cancer had a stronger familial/genetic component (relative risk (RR) 1.47) than rectal cancer (RR 0.98). The familial/genetic component appeared stronger for proximal colon cancer than for distal colon cancer only among women (RR 2.24 v RR 1.45). CRC appeared to be positively associated with leukaemia (RR 1.77), stomach cancer (RR 1.32), and testicular cancer (RR 3.13), and negatively associated with urinary bladder cancer (RR 0.57) within families. The cancer spectrum associated with CRC among younger participants included prostate (RR 1.93), uterus (RR 2.49), and thyroid (RR 3.85) cancers. Conclusion: If our results are confirmed, follow up guidelines for patients with a family history of CRC should depend on the sex and tumour site of affected relatives to avoid needless invasive screening.